IGFBP-3 Interacts with the Vitamin D Receptor in Insulin Signaling Associated with Obesity in Visceral Adipose Tissue - Moreno-Santos, Inmaculada; Castellano Castillo, Daniel; Lara, María Fernanda; Fernández-García, José Carlos; Tinahones-Madueño, Francisco José; Macías-González, Manuel (MDPI, 2017)
Adipose tissue has traditionally only been considered as an energy storage organ. Nevertheless, the importance of this tissue in systemic physiology and, especially, in systemic inflammation has been highlighted in recent years. Adipose tissue expresses proteins related to vitamin D (VD) metabolism, and it has been proposed that it can act as a VD storage tissue. The active form of VD, 1,25-dihydroxyvitamin D3 (1,25(OH)₂D₃), is able to modify adipocyte and adipose tissue physiology via the VD receptor (VDR), decreasing the expression of pro-inflammatory cytokines in adipose tissue. Moreover, VD deficiency and VDR has been reported to be associated with obesity and diabetes. However, the results of the different studies are not conclusive. Insulin growth binding proteins (IGFBPs) have been identified in adipose tissue, but their roles are poorly understood. Therefore, the objective of this study was to analyze the plasma levels of VD and the gene expression of VDR in the adipose tissue of subjects with morbid obesity (MO) and with different degrees of insulin resistance (IR), as well as the functionality of direct interaction between IGFBP-3 and VDR, which could explain its inhibitory role in adipogenesis. Our results show a novel role of the VD system in the regulation and activation of IGFBP-3 in visceral adipose tissue (VAT) of patients with MO, as a new and alternative mechanism proposed in the insulin signaling associated with obesity.
Keywords: Resistencia a la insulina; Síndrome metabólico; Vitamin D; VDR; IGFBP; Insulin resistance; Morbid obesity and adipose